VisioAux: a crowdsource approach for accessibility evaluation in mobile devices - Ramos Barboza, Alex Frederico; Eler, Marcelo Medeiros (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2025: Anais do XXIV Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2025)
Introduction: The rapid growth in mobile device usage has increased the need for accessible applications. Automated accessibility testing approaches were developed to support accessibility evaluation, but they have limitations such as low coverage of features and screens and the lack of prioritization of issues by real-world impact. Objective: This paper introduces an automated crowdsourcing-based strategy to increase coverage and provide impact-based prioritization of accessibility issues in mobile applications. Method: We developed VisioAux, an accessibility testing service integrated into mobile apps and deployed on end users’ devices. As users navigate apps in their daily activities, VisioAux performs runtime accessibility checks on apps under test. VisioAux collects reports from multiple devices and consolidates results to estimate coverage and issue severity for a given app. Results: A preliminary evaluation compared VisioAux with Google Accessibility Scanner, assessed its performance impact, and verified its crowdsourcing capabilities. Results indicate comparable detection performance, negligible performance overhead, and successful aggregation of accessibility reports from diverse devices.